CREAMY: Krim Ekstrak Biji Bengkuang (Pachyrhizus Erosus) Sebagai Alternatif Obat Antimyiasis Yang Aman, Efektif, Dan Ekonomis - Rina Astuti; Yoga Rivaldi; Nabillah Ananda Sakinah; Annisa Zikriatin Nafilah; Seftian Syahri Putra (UII, 2017)
Myiasis is a disease caused by infestation of fly larvae (Chrysomya bezziana) in living tissue of homoeothermic animals. Myiasis can cause stress and reduction of livestock productivity. The prevalence of myiasis in Indonesia is high, both in extensive and intensive livestock. Current spray-formulated antimyiasis drug in the market today is offered at high price. CREAMY is antimyiasis cream with yam bean seed extract that contains 0.5-1.0% rotenone active substance. The goal of this program is to create safe, effective, and economic antimyiasis cream. This program was conducted from March to July 2017. The methods implemented include preparation of ingredients, extraction, cream making, packaging, and marketing. Extraction consists of maceration and evaporation. Cream making consists of extract and cream base weighing with 2% extract and 98% cream base; and homogenization. Cream was packaged in 20 gram pots and sold at Rp30.000 each pot. Marketing strategy consists of door-to-door method, reselling, retail, online selling, and active participation in livestock expo. The number of products sold within five months has reached 142 units with a turnover of Rp5.618.980. The result of observation to breeders indicates that the use twice in a day can cure minor and moderate wounds (in two days) so that CREAMY is effective to heal myiasis and outside wounds, and is also well-accepted by customers. The business is very prospective due to high and varied prevalence of myiasis. In order to improve the performance, the enhancement of product quality, quantity, and variations for many kinds of terrestrial animals is needed.